“Unidades De Negocio Como Fuente De Emprendimiento Y Su Incidencia En Las Prácticas Profesionales De Los Estudiantes De La Facultad De Admnistración, Finanzas E Informática De La Universidad Técnica De Babahoyo” - MUÑOZ OVIEDO, LORENA (2013)
This thesis condenses in content a clear view of the problem on the process of internships or work experience for students, the same as not being made in their respective professional profiles, and happens not to be a sufficient supply companies to cover the amount of students in the process of conducting. It is important that the graduate of a professional career have training and practical development in the area in which they will play like a professional, and what better to do on a real stage, and; that through this visualize a better opportunity to develop their mental skills related to their profile. Among the main problems outlined in the working paper presented here can be identified: Students are not doing their internships or work experience in their profile, time to perform them usually lasts for not being one sufficient bank companies which perform internships or practical internships are not projecting get a glimpse of entrepreneurship in the race to conclude, resulting in the graduate professional not start a business but seeking employment in the vast majority is little practical for being the very low labor market in number of graduates professionals.